Effect of Acid Concentration on the Activation of Bayah Natural Zeolite for Palm Kernel Shell Pyrolysis Application - Endang Suhendi; Andre Wibowo; Tia Lestari; Teguh Kurniawan (Reaktor, 2020)
Biooil is the main product in the pyrolysis process which is expected to be a liquid fuel replacement solution. But the resulting biooil cannot be directly used as a result of high oxygenated compounds, high viscosity, corrosive, and unstable. Addition of activated natural zeolite catalyst to the pyrolysis process is expected to improve the quality of biooil in order to be used as a renewable liquid fuel. The research aims to determine the influence of acid concentrations on zeolite modification to the characteristics of pyrolysis products. Result of catalyst characterization indicates that zeolite activation using acid will increase Si/Al ratio as well as open the surface of previously hindered zeolite. The yield of char produced in this study tends not to undergo significant changes between the catalytic and noncatalytic pyrolysis by 33% wt. Addition of zeolite catalyst in pyrolysis proved to be able to increase the content of phenol and decrease the content of acetic acid in bio-oil by 6% . Meanwhile, yield of CO2 increases by 20% in the use of catalysts due to the release of oxygen in the oxygenate compounds. The results of this study showed that the resulting biooil still does not meet the specifications of liquid fuels but can be utilized as a renewable chemical feedstock.Keywords: pyrolysis; biomass; natural zeolite;modified